Police departments and care continuity for autistic youth in suicidal crisis. Issue 3 (22nd April 2022) - McGhee Hassrick, Elizabeth; Weissinger, Guy; VanFossen, Catherine; Milani, Rose; Ventimiglia, Jonas; Hoffman, Isaiah Delane-Vir; Wintersteen, Matthew; Atte, Tita; Fernandes, Sherira; Diamond, Guy
Abstract : Purpose: Autistic youth face higher risks for experiencing mental health crises. To develop and test a county-level social network measure of care coordination between police departments and other systems that support autistic youth experiencing suicidal crisis. Design/methodology/approach: To measure the structure of care coordination for autistic youth experiencing suicidal crisis, the authors created a roster of all police departments and youth servicing organizations in two East Coast counties in the United States. They met or exceeded the whole network recruitment threshold of 70% completion in both counties. From the data, the authors created a directed matrix for each county of all reported connections, which they used to create sociograms and calculate standard network measures, including indegree, outdegree and total degree for each organization in the network. Data management and processing were done using R-programming and ORA. Findings: Social network findings indicated that about half of all police departments surveyed coordinate care for autistic youth in suicidal crisis. Coordination varied by county, with nonpolice organizations acting as connectors between police and other nonpolice organizations. Two structural configurations were found, including a nonpolice organizational hub structure and a lead police structure. More research is needed to determine how different police integration structures shape care coordination for autistic youth. Research limitations/implications: Limitations include the small number of counties included in the study. A larger sample of counties is required for generalizable results. Practical implications: This article introduces new tools and approaches to assist police in building their capacity to measure and improve their coordination of care with other community systems during crisis situations for youth on the autism spectrum. Network science (e.g. matrix and graph theoretic algebra methods) can be used to measure the configuration of relationships police departments have with complex multi-level healthcare systems. Social implications: Implications for findings include the consideration of police integration across systems in ways that produce new collaboration possibilities to support autistic youth experiencing suicidal crisis. Originality/value: While police departments play a critical role in coordinating care for youth in suicidal crisis, little is known if or how police departments collaborate with other systems to provide assistance for autistic youth during a suicidal crisis. Improving care continuity within and between systems could potentially address clinical and structural challenges and reduce risk for autistic youth experiencing a suicidal crisis.